Study on Genre of Contemporary Literary Fiction in Campus Novel: - (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This is paper genre of contemporary literary fiction in compus novel achieved appeal evenbefore it was classified and labelled. Those writings, however, do not qualify as college novels. It wasn'tuntil the second half of the twenty-first century that this new genre of campus novels began to attract theattention of both authors and readers. Despite its wealth of literature, India is still in the early stages ofdevelopment, as many new Indian authors have dabbled in this genre. Modern Indian authors, with theirdeep interest in inquisitively investigating fresh issues, have begun to prove their strength in this genreas well in the early twenty-first century.